O trabalho institucional na construção social da identidade turística do município de Conde-PB - Albuquerque, Mariene Cavalcante Borba de (2020)
This work aimed to understand how the process institutional work of the social construction of the Conde (PB) municipality tourist identity was occurred, which, despite being the second place to receive tourists in the state of Paraíba, is considered as a tourist route, and not as the final destination. In order to answer research problem, the following steps were taken: (i) mapping of the organizational actors and their respective roles in the Conde (PB) municipality tourist identity; (ii) verification of the practices, processes, and mechanisms pertinent to institutional work that are responsible for the social construction of the tourist identity of Conde (PB); and, (iii) identification of elements that evidence the Conde (PB) tourist identity. Sociological-based Organizational Institutionalism, which studies how external social pressures influence the behavior of organizations, constituted the main theoretical framework of reference. In it, the concept of 'institutional work' was central; it has the agency of the actors and social practices as its main foundations, it occurs in organizational fields, creating, maintaining or interrupting institutions, in areas that can be symbolic, relational or material. These actions take place according to the context in which the organizations are inserted, being, thus, socially constructed, and, as they are molded and adapted to an institutionalized identity, they acquire institutional legitimacy. This research was configured as a qualitative case study, of a descriptive-exploratory character, and used qualitative content analysis on the empirical material obtained through primary sources (informal conversations, observation and interviews with semi-structured scripts) and secondary (documents). The research was able to portray what actions have been taken by the actors in the organizational field that could indicate a process of construction of the local tourist identity based on attributes of centrality, distinctiveness and temporality that characterize this identity. It was concluded that the municipality of Conde has a diverse identity framework in which heterogeneous actors, with distinct end activities, have carried out individual and non-collaborative actions indicating a multi-identity construction process, which has prevented it from becoming a tourist attraction competitive of becoming a final tourist destination.